PENGARUH MODAL, LOKASI DAN JENIS DAGANGAN TERHADAP PENDAPATAN PEDAGANG PADA PASAR BORONG KABUPATEN MANGGARAI TIMUR - Welda, Flaviani Yartini; Marselina, Apriana (Program Studi Akuntansi Universitas Flores, 2023)
The purpose of this study was to determine the effect of capital, location and type of merchandise on the income of traders in the Borong market, East Manggarai Regency. The population in this study were all traders in Pasar Borong, East Manggarai Regency, totaling 458 traders. The sampling technique used purposive sampling, namely a sampling technique in which the sampling method was determined using certain characteristics, totaling 82 traders. This type of research uses quantitative research. This study uses primary data, namely a questionnaire. Data were analyzed using multiple linear regression analysis which was processed using IBM SPSS Statistics ver 25. The results of this study indicate that: (1) Capital affects the income of traders, this is evidenced by the regression coefficient value of the capital variable of 0.214 with tcount > ttable (2.728 > 1.990) and a significant level of 0.008 <0.05. (2) Location affects the income of traders, this is evidenced by the value of the regression coefficient of the location variable of 0.188 with tcount > ttable (2.797 > 1.990) and a significant level of 0.006 <0.05. (3) The type of trade affects the income of traders, this is evidenced by the value of the regression coefficient of the type of trade variable of 0.314 with tcount > ttable (3.235 > 1.990) and a significant level of 0.002 <0.05. Simultaneously the variables of capital, location and type of merchandise affect the income of traders by 26.7% while the remaining 73.3% is influenced by other variables not explained in this study.